Transanal versus conventional total mesorectal excision for rectal cancer using the IDEAL framework for implementation. Issue 2 (22nd April 2021) - Robertson, R L; Karimuddin, A; Phang, T; Raval, M; Brown, C
Abstract: Background: Transanal total mesorectal excision (TaTME) is an innovative technique for distal rectal cancer dissection. It has been shown to have similar short-term outcomes to conventional open and laparoscopic total mesorectal excision (cTME), but recent studies have raised concern about increased morbidity and local recurrence rates. The aim of this study was to assess outcomes after TaTME versus cTME for rectal cancer. Methods: TaTME was implemented in 2014 using IDEAL principles in a single institution. The institution maintains databases for all patients undergoing rectal cancer surgery. This retrospective review compared data collected from all patients who had TaTME with those from a propensity-matched cohort of patients who underwent cTME. The primary outcome was a composite pathological measure combining margin status and quality of total mesorectal excision (TME). Short-term clinical and survival outcomes were also measured. Results: Propensity matching created 109 matched pairs for analysis. Nine patients (8.3 per cent) undergoing TaTME had positive margins and/or incomplete TME, compared with 11 (10.5 per cent) undergoing cTME ( P  = 0.65). There were no significant differences in morbidity between the TaTME and cTME groups, including number of anastomotic leaks (13.8 versus 18.3 per cent; P = 0.37). The estimated 3-year local recurrence-free survival rate was 96.3 per cent in both groups ( P  = 0.39). Estimated 3-year overall (93.6 per cent for TaTME versus 94.5 per cent for cTME; P  = 0.09) and disease-free (88.1 versus 76.1 per cent; P  = 0.90) survival rates were similar. Conclusion: TaTME provided similar outcomes to cTME for rectal cancer with the application of IDEAL principles. Abstract : This study assessed the outcomes of a single-institution prospectively collected cohort of patients undergoing transanal total mesorectal excision (TaTME) for rectal cancer, compared with a propensity-matched cohort of patients undergoing conventional surgery. Methods from the IDEAL framework were used to institute TaTME. There were no significant differences in histopathological, clinical or survival outcomes between the two groups.